Binding of Vav to Grb2 through dimerization of Src homology 3 domains. - Ye, Z S (1994)
The protooncogenic protein Vav has the structure of an intracellular signal transducer. It is exclusively expressed in cells of hematopoietic lineage and plays a crucial role in hematopoietic cell differentiation. Here we report that both in cell extracts and within intact mammalian cells Vav binds to Grb2 (Sem-5/ASH/Drk), an adaptor molecule which plays a key role in Ras activation. The interaction became evident from a yeast two-hybrid screen and its specificity was demonstrated by in vitro binding assays. It is mediated by an unusual protein-protein binding reaction: dimerization of specific intact Src homology 3 domains of each of the partners. Signaling during hematopoietic lineage differentiation may therefore involve the tissue-specific signal transducer Vav linking into the ubiquitous pathway involving Grb2 and ultimately Ras.